Servant Leadership Model of School Principals in Enhancing Teacher Performance at SMAN 1 Gerung - Dhomroh, Siti; Fitriani, Mohamad Iwan; Thohri, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explain two things: (1) teachers' perceptions of servant leadership and (2) the implementation of servant leadership models by the school principal to enhance teacher performance at SMAN 1 Gerung, West Lombok Regency. The approach in this research is qualitative. The research is conducted at SMAN 1 Gerung. Data collection techniques involve interviews and observations. The results of this research show teachers' perceptions of the servant leadership model. They perceive that a school principal with servant leadership qualities possesses the ability to listen, empathy, openness, and community building. Additionally, the implementation of the servant leadership model at SMAN 1 Gerung is carried out by creating a supportive and motivating environment, empowering teachers' potential, and understanding and listening to teachers' aspirations. The servant leadership model has gained recognition in the field of education for its focus on service delivery, self-development, and individual empowerment. Servant Leadership is also in line with Islamic teachings as mentioned in the Quran Surah Asy-Syu’ara (26:215), Ali Imran (3:159), and has been exemplified by the Prophet Muhammad SAW.